CULTURAL AND RELIGIOUS ACCULTURATION IN THE RAMBU SOLO’ CEREMONY MUSLIM IN TANA TORAJA - Syam, Futri; Husna, Fathayatul (Penamas, 2025)
This study examines cultural acculturation in the Rambu Solo’ funeral tradition in Tana Toraja, South Sulawesi, as adapted by Muslim families. This study discusses the challenges of cultural and religious acculturation, considering the potential for polemics when there is no space for dialogue, negotiation, and mutual understanding. To study this research, a qualitative descriptive method was used, and data were collected through in-depth interviews, observation, and documentation. The results of this study are that Rambu Solo’ is a sacred and meaningful traditional funeral ceremony usually performed by adherents of the Aluk Todolo religion and Christians. However, over time, this tradition has also begun to be practiced by Muslims, with several adjustments to align with Islamic law, including the elimination of elements that conflict with Islamic teachings, such as the absence of pork, replacing singing with recitation of the Qur'an, the elimination of alcoholic beverages (ballo'), and the elimination of the buffalo fighting ritual (mappasilaga tedong). Islamic rituals carry out the process of slaughtering animals. Initially, the implementation of Rambu Solo’ for Muslims sparked controversy because it was considered inconsistent with Islamic law.